54th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2013
DOI: 10.2514/6.2013-1825
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Design Phase I Summary for the NASA Composite Cryotank Technology Demonstration Project

Abstract: A description of the Phase I structures and design work of the Composite Cryotank Technology Demonstration (CCTD) Project is in this paper. The goal of the CCTD Project in the Game Changing Development (GCD) Program is to design and build a composite liquid-hydrogen cryogenic tank that can save 30% in weight and 25% in cost compared to state-of-the-art aluminum metallic cryogenic tank technology when the wetted composite skin wall is at an allowable strain of 5000 µin/in. Three Industry teams developed composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…The applications of CFRP cryogenic tanks have been studied for over the past two decades. [1][2][3][4][5][6][7][8][9] Although the required pressure is low compared with general purpose highpressure vessels, a CFRP tank is exposed to cryogenic temperatures. Moreover, because the curing temperature of high-performance CFRP is approximately 180 C, a difference in the thermal expansions of carbon fibres and resins evolves non-negligible thermomechanical stresses, which were also influenced by the cure shrinkage and vitrification, and tool-part interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of CFRP cryogenic tanks have been studied for over the past two decades. [1][2][3][4][5][6][7][8][9] Although the required pressure is low compared with general purpose highpressure vessels, a CFRP tank is exposed to cryogenic temperatures. Moreover, because the curing temperature of high-performance CFRP is approximately 180 C, a difference in the thermal expansions of carbon fibres and resins evolves non-negligible thermomechanical stresses, which were also influenced by the cure shrinkage and vitrification, and tool-part interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the four industry teams (Boeing, Lockheed Martin, and Northrop Grumman) were tasked with developing composite cryotank designs. [1][2][3] The NASA team developed an aluminum lithium alloy cryotank design that incorporated Technology Readiness Level 4 (TRL) 9 structural design methodology, materials, and manufacturing techniques to serve as a reference design for comparison to the composite cryotank designs. The reference design was based heavily on the Space Shuttle Super LightWeight Tank 5 (SLWT) and the Ares I liquid hydrogen (LH2) tank.…”
Section: Introductionmentioning
confidence: 99%
“…A cost analysis effort showed that 20-25% cost saving can be achieved by utilizing an automated fiber placement process [20].…”
Section: Cctd Composite Cryotankmentioning
confidence: 99%
“…NASA worked with four competing industry partners-ATK, Boeing, Lockheed Martin, and Northrop Grumman at the design phase of the project with the aim to reduce weight by 30%, reduce cost by 25%, and withstand a strain of 0.005 [20]. Four competing conceptual designs differing in materials, structures, manufacturing processes were assessed through coupon testing and finite element stress analysis.…”
Section: Cctd Composite Cryotankmentioning
confidence: 99%